2012
DOI: 10.1111/tpj.12032
|View full text |Cite
|
Sign up to set email alerts
|

The ammonium/nitrate ratio is an input signal in the temperature‐modulated, SNC1‐mediated and EDS1‐dependent autoimmunity of nudt6‐2 nudt7

Abstract: SUMMARYAtNUDT7 was reported to be a negative regulator of EDS1-mediated immunity in Arabidopsis. However, the underlying molecular and genetic mechanism of the AtNUDT7-regulated defense pathway remains elusive. Here we report that AtNUDT7 and its closest paralog AtNUDT6 function as novel negative regulators of SNC1, a TIR-NB-LRR-type R gene. SNC1 is upregulated at transcriptional and possibly post-transcriptional levels in nudt6-2 nudt7. The nudt6-2 nudt7 double mutant exhibits autoimmune phenotypes that are m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 80 publications
0
41
0
Order By: Relevance
“…Notably, MS salt medium contains both ammonium and nitrate as nitrogen sources, whereas nitrate is the predominant source of nitrogen in soil due to microbial nitrification (Bloom, 2015). In this context, it has previously been shown that there is an interaction between defense responses and nitrogen metabolism (Park et al, 2011;Wang et al, 2013). Specifically, the developmental phenotypes observed in these aforementioned studies were caused by a low ammonium-to-nitrate ratio and could be repressed by simple ammonium supplementation.…”
Section: The Lack Of Pdx3 Renders the Plant With An Ammoniumdependentmentioning
confidence: 71%
“…Notably, MS salt medium contains both ammonium and nitrate as nitrogen sources, whereas nitrate is the predominant source of nitrogen in soil due to microbial nitrification (Bloom, 2015). In this context, it has previously been shown that there is an interaction between defense responses and nitrogen metabolism (Park et al, 2011;Wang et al, 2013). Specifically, the developmental phenotypes observed in these aforementioned studies were caused by a low ammonium-to-nitrate ratio and could be repressed by simple ammonium supplementation.…”
Section: The Lack Of Pdx3 Renders the Plant With An Ammoniumdependentmentioning
confidence: 71%
“…58) A more recent study reported that Arabidopsis sensed the ammonium/nitrate ratio as an input signal to determine the amplitude of the EDS1-mediated immune defense response, possibly through the modulation of NO production, in which both AtNUDX6 and AtNUDX7 act as negative regulators. 55) Although SA levels were higher in KO-nudx7 plants than in wildtype and KO-nudx6 plants, double KO-nudx6/nudx7 plants accumulated markedly greater amounts of SA than KO-nudx7 plants and exhibited the dwarf phenotype caused by autoimmunity depending on EDS1 and SNC1, the Toll/Interleukin-1 receptor-nucleotidebinding leucine-rich repeat (TIR-NB-LRR)-type R gene. These findings suggested that AtNUDX6 may act synergistically on the EDS1-mediated plant immune response and accumulation of SA regulated by AtNUDX7.…”
Section: Regulation Of Biotic Stress Responsesmentioning
confidence: 99%
“…49,57) However, growth retardation was observed in KO-nudx7 plants, but not KO-nudx6 plants grown on soil, and this was attributed to the hyperaccumulation of SA and H 2 O 2 leading cell death. 55,56) Jambunathan et al 52) indicated that the growth phenotypes of KO-nudx7 plants were due to differences in nutrient compositions; no phenotypic difference was observed between KO-nudx7 and wild-type plants in nutrient-rich medium. Zeng et al 64) reported that KO-nudx7 plants accumulated high levels of ABA, resulting in a reduced seed germination phenotype.…”
Section: Regulation Of Biotic Stress Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly in this context, exogenous ammonium (but not nitrate) has been shown to alleviate autoimmune phenotypes. 10,11 Moreover, perturbations in nitrogen metabolism may result in autoimmunity. For instance, a mutant in the ammonium transporter amt1.1 displays an autoimmune phenotype.…”
Section: Introductionmentioning
confidence: 99%